2014
DOI: 10.1097/eja.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levobupivacaine on articular chondrocytes

Abstract: In-vitro 0.5% levobupivacaine is more chondrotoxic than saline in human articular cartilage after 1 h of exposure. Bupivacaine seems to be less chondrotoxic than levobupivacaine. With shorter exposures, no clear chondrotoxic effect was shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
9
2
Order By: Relevance
“…They found that exposure to 0.5% bupivacaine for 15 or 30 minutes did not affect chondrocyte viability; however, when the exposure time was increased to 1 hour, there was more chondrotoxicity noted when compared to normal saline controls (20.7 ± 10.4% compared to 9.6 ± 5%). However this finding was not statistically significant . In this study, 0.5% levobupivacaine showed greater trends toward chondrotoxicity than 0.5% bupivacaine did …”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations
“…They found that exposure to 0.5% bupivacaine for 15 or 30 minutes did not affect chondrocyte viability; however, when the exposure time was increased to 1 hour, there was more chondrotoxicity noted when compared to normal saline controls (20.7 ± 10.4% compared to 9.6 ± 5%). However this finding was not statistically significant . In this study, 0.5% levobupivacaine showed greater trends toward chondrotoxicity than 0.5% bupivacaine did …”
Section: Resultscontrasting
confidence: 71%
“…However this finding was not statistically significant . In this study, 0.5% levobupivacaine showed greater trends toward chondrotoxicity than 0.5% bupivacaine did …”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…Previous meta-analyses have demonstrated that the single-dose IA morphine34, bupivacaine567, ropivacaine8, clonidine9 or the combination of morphine and bupivacaine1011 were effective in pain relief. However, it is commonly known that IA local anesthetics must be used cautiously due to the concern of chondrotoxicity12, especially for bupivacaine13141516171819, levobupivacaine131419, ropivacaine13141617, mepivacaine17 and lidocaine13161820.…”
mentioning
confidence: 99%